Herbal cure for the leukemia- A challenging progression - Kirthika Dhanraj; Anitha Joseph; Renuka Saravanan; Sivakumar Ramalingam (Journal of Global Pharma Technology, 2018)
Traditional medicine system is still used by approximately 65-80% of the world’s population in developing countries because of its fewer side effects. Most of the molecules derived from plants are effective against different cancer with different targets. The review mainly deals different plants such as Alisma orientale, Annona glabra L, Tinospora cordifolia, Euphorbia formosana Hayata which are used in the treatment of leukemia. It throws light on the therapeutic efficacy of different plant molecules such as berberine, flavanoids, caffeic acid and kolavirion with the mode of action in different cells, which have already been used for the treatment of leukemia. This review will promote research towards the development of plant based drugs which could be used for the treatment for the cancer.Key words: Leukemia, Medicinal plants, Phytoconstituents and HL-60.